INTERNATIONALIZATION OF EDUCATION AS HIGH-PRIORITY ACTIVITIES OF THE UNIVERSITY - Anton N. Grigoriev; Georgy V. Korshunov (Высшее образование в России)
This article considers different aspects in building the export policy of educational services in the global education market and the education of international students in Russian universities. The article is aimed at emphasizing the growing attention of the universities to this kind of activities and the expansion of the borders of the current cooperation in the area of educational services for international students in Russia. We consider the issues of attracting and recruiting of international students among the compatriots and their staying in the region after the study in order to solve the demographic problem in regions, to meet a lack of professionals in technical areas, to reunify with the native nation. The authors present the experience of Ukhta State Technical University in international partnership, analyze the Russian and foreign universities' practice in such issues as how to recruit, attract and work with international students. In addition, the problems and difficulties they face are considered.